Failure Control Of A Skyscraper Using Different Methods Of Retrofitting - Kumar, Kujala Pranith; Rama Prasad, C.Venkata Siva (Journal of Neonatal Surgery, 2025)
A skyscraper is a tall, continuously habitable building having multiple floors. The term was originally used to describe one of at least 35-50 floors, mostly designed for office, commercial and residential uses. A skyscraper can also be called a high-rise, but the term skyscraper is often used for buildings higher than 50 m (164 ft). One common feature of skyscrapers is having a steel framework that supports curtain walls. These curtain walls either bear on the framework below or are suspended from the framework above, rather than load-bearing walls of conventional construction. The load a skyscraper experiences is largely from the force of the building material itself. In most building designs, the weight of the structure is much larger than the weight of the material that it will support beyond its own weight. In technical terms, the dead load, the load of the structure, is larger than the live load. The basic principles of design for vertical and lateral loads (wind & seismic) are the same for low, medium or high rise building. But a building gets high, both vertical & lateral loads become controlling factors. The vertical loads increase in direct proportion to the floor area and number of floors. In contrast to this, the effect of lateral loads on a building is not linear and increase rapidly with increase in height. Due to these lateral loads, deflection & moments on steel components will be very high. By retrofitting the structure, these types of failures can be controlled In the present analysis, a Skyscraper with 40 floors will be analyzed. It will be tested by different methods of retrofitting like shear walls, bracings and fixed dampers at different locations. The building will be considered on medium soil and analyzed in all the four zones. Moments, Drift, Torsion and storey shear will be compared for all the cases. A commercial package, ETABS will be used for analyzing Skyscraper of 120m height and for different zones. The results will be compared using tables & graphs to find out the most optimized solution.